The Concept of Islamic Social Finance Development Based on Financial Technology to Realize a Prosperous Society - Marwini, Marwini; Salam, Annisa Nur (Jurnal Ilmiah Ekonomi Islam, 2023)
Prosperity is a great goal that every country in the world aspires to. However, this condition will certainly not be achieved without a problem called poverty. If you look at the available data, about 30% of the world's population (1.56 billion) lives in multidimensional poverty; 50% of the world's population (3 billion) lives on less than $2.5 a day; And 80% of the world's population lives on less than $10 a day. This shows that Welfare in the world is only enjoyed by a small part of the population. A study published that OIC (Organization of Islamic Cooperation) member countries generally have a lower HDI (Human Development Index) than non-OIC countries. If viewed further, Islam has various solutions to avoid poverty through Islamic social finance instruments. Zakat, Infaq, and Waqf have great potential to be developed to prosper the community. So, in this paper, we will discuss the financial technology model used to develop the role of Islamic social finance instruments such as Zakat, infaq, and waqf. So that social and financial institutions can continue to develop various empowerment programs to prosper the community.